2009
DOI: 10.1007/s11657-009-0034-8
|View full text |Cite
|
Sign up to set email alerts
|

Psychological state, quality of life, and body composition in postmenopausal women with osteoporosis in Lithuania

Abstract: SummaryThe objective of this study was to determine body composition, physical activity, and psychological state in postmenopausal women with osteoporosis. Fat mass, lean mass, water mass, and basal metabolic rate are lower, self-reported physical activity and risk factors of fractures are higher, and cognitive functions were worse in osteoporotic patients than in controls. Significant correlations were found between physical activity and emotional state parameters.IntroductionThis study aims to determine pecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 32 publications
(35 reference statements)
2
9
0
4
Order By: Relevance
“…Peki depresyon mu artmış kemik kaybı için risk faktörüdür yoksa artmış kemik kaybı mı osteoporoz için risk faktörüdür? sorusu tam açıklığa kavuşturulamasa da net ilişkileri birçok kez ortaya konulmuştur (1)(2)(3). Bu çift yönlü ilişkinin bir başka boyutu ise hem depresyon hem de osteoporoz bireyin yaşam kalitesini kötüleştirmektedir (2)(3)(4).…”
Section: Introductionunclassified
See 2 more Smart Citations
“…Peki depresyon mu artmış kemik kaybı için risk faktörüdür yoksa artmış kemik kaybı mı osteoporoz için risk faktörüdür? sorusu tam açıklığa kavuşturulamasa da net ilişkileri birçok kez ortaya konulmuştur (1)(2)(3). Bu çift yönlü ilişkinin bir başka boyutu ise hem depresyon hem de osteoporoz bireyin yaşam kalitesini kötüleştirmektedir (2)(3)(4).…”
Section: Introductionunclassified
“…sorusu tam açıklığa kavuşturulamasa da net ilişkileri birçok kez ortaya konulmuştur (1)(2)(3). Bu çift yönlü ilişkinin bir başka boyutu ise hem depresyon hem de osteoporoz bireyin yaşam kalitesini kötüleştirmektedir (2)(3)(4). Şimdiye kadar ki bu konuda yapılmış çalışmalarda araştırma örneklemini ya premenapozal ya da postmenapozal kadınlar oluşturmaktaydı (2)(3)(4).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…[30][31][32] The ability of the person to perform activities depends on his/her body structure and composition, joint and other pains, and working status. 33,34 In our study, it was observed that the physical domain of QoL had a moderate inverse correlation with the BMI in the rural postmenopausal women and a good inverse correlation in urban postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Lasaite et al the QOL of postmenopausal women with osteoporosis was analyzed using WHOQOL-BREF. They did not find significant differences in QOL of osteoporotic patients and healthy controls [100].…”
Section: E Other Risk Factorsmentioning
confidence: 84%